The Disparity Of Judge's Decisions In The Same Criminal Act Of Corruption - Wahyuni Malanua (Universitas Negeri Gorontalo, 2021)
The purpose of this study is to find out what are the factors that cause the disparity of criminal sanctions in the verdict of criminal acts of corruption as well as the legal basis that becomes the consideration for making decisions on corruption crimes by judges, especially in the Gorontalo District Court.The type of research used is normative juridical research, with a statutory and conceptual approach, for this approach several primary legal materials are used, namely laws and regulations relevant to the object of study supported by secondary legal materials in the form of books, journals and other sources. . The conclusion of this study found that there were differences in the results of the comparison of two different decisions where the Gorontalo District Court Decision Number 18/Pid.Sus-TPK/2020/PNGto which harmed the state by 43 billion was only given a sanction of 1 year 6 months in prison while in decision number 1/ Pid.sus -TPK/2018/PNGto which harms the state as much as 1 billion is given a prison sentence of more than 4 years so that this can be said to be a disparity of decisions.